A Prospective Longitudinal Assessment of Medical Records for Diagnostic Substitution among Subjects Diagnosed with a Pervasive Developmental Disorder in the United States - Geier, David A.; Kern, Janet K.; Hooker, Brian S.; Sykes, Lisa K.; Geier, Mark R. (Frontiers in Pediatrics, 2015)
Background: Previously, investigators suggested that diagnostic substitution from other diagnoses, e.g., mental retardation (MR) and/or cerebral palsy (CP) to pervasive developmental disorder (PDD) is a driving factor behind increases in PDD. This study evaluated potential diagnostic substitution among subjects diagnosed with PDD vs MR or CP by examining birth characteristic overlap. Methods: SAS® and StatsDirect software examined medical records for subjects within the Vaccine Safety Datalink (VSD) database who were Health Maintenance Organization (HMO)-enrolled from birth until diagnosed with an International Classification of Disease, 9th revision (ICD-9) outcome of PDD (299.xx, n=84), CP (343.xx, n=300), or MR (317.xx, 318.xx, or 319.xx, n=51). Results: Subjects with PDD had significantly (p<0.01) increased: male/female ratio (PDD=5.5 vs CP=1.5 or MR=1.3), mean age of initial diagnosis in years (PDD=3.13 vs CP=1.09 or MR=1.62), mean gestational age in weeks at birth (PDD=38.73 vs CP=36.20 or MR=34.84), mean birth weight in grams (PDD=3,368 vs CP=2,767 or MR=2,406), and mean Appearance-Pulse-Grimace-Activity-Respiration (APGAR) scores at 1 minute (PDD=7.82 vs CP=6.37 or MR=6.76) and 5 minutes (PDD=8.77 vs CP=7.92 or MR=8.04), as compared to subjects diagnosed with CP or MR. Conclusion: This study suggests diagnostic substitution cannot fully explain increased PDD prevalence during the 1990s within the United States.